2015
DOI: 10.1016/j.jacc.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Across the Life Course and Cardiometabolic Risk

Abstract: Psychological distress at any point in the life course is associated with higher cardiometabolic risk. This is the first study to suggest that even if distress appears to remit by adulthood, heightened risk of cardiometabolic disease remains. Findings suggest early emotional development may be a target for primordial prevention and for promoting lifelong cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 27 publications
6
66
1
Order By: Relevance
“…Specifically, epidemiological studies indicate that adults exposed to ELS develop several risk factors for cardiovascular and metabolic disease including elevated systolic blood pressure (SBP), BMI, waist circumference, and resting HR 11,13,14,42 . Moreover, ELS has a positive correlation with the clustering of metabolic risk biomarkers such as higher circulating levels of leptin and the acute phase proinflammatory mediator, C reactive protein (CRP), as well as elevations in plasma glucose and insulin 4345 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, epidemiological studies indicate that adults exposed to ELS develop several risk factors for cardiovascular and metabolic disease including elevated systolic blood pressure (SBP), BMI, waist circumference, and resting HR 11,13,14,42 . Moreover, ELS has a positive correlation with the clustering of metabolic risk biomarkers such as higher circulating levels of leptin and the acute phase proinflammatory mediator, C reactive protein (CRP), as well as elevations in plasma glucose and insulin 4345 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the Georgia Stress and Heart Study (GSH) including 213 African Americans and 181 European Americans, revealed that individuals exposed to multiple ELS factors display a greater increase in blood pressure (BP) levels compared to control individuals in a 23-year follow up period 12,13 . Furthermore, the 1958 British Birth Cohort Study including 6,714 members, revealed that metabolic risk was higher among people with psychological distress in childhood only and persist across the life course 14 More recent studies highlighted that when the environment is harsh and unpredictable, a fast life history strategy is adaptive. That is, in these environments, somatic efforts are unsuitable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there may be periods during which exposure to adversity or psychological distress is highly toxic in relation to physical health, or periods during which damage incurred is more difficult to reverse. One recent study found that high levels of distress in childhood, even when distress was lower during adulthood, had substantial impact on cardiometabolic health in middle adulthood (Winning et al , 2015). Other research has similarly suggested that exposure to adversity during pregnancy and early childhood leads to damage relatively early on, and may be especially deleterious for long-term health (Ehlert, 2013).…”
Section: New Research Directionsmentioning
confidence: 99%
“…It is well documented that childhood exposure to certain potentially stressful life events (SLEs) put them at a higher risk of distress (negative stress) which then may increase the risk of  adverse health outcomes and poor quality of life [1, 2]. Children of all ages experience stressful life events, but the type and the way a child or youth express their persisting stress depend  on their age, gender, level of development, and the individual’s threshold for responses to stressful stimuli [3].…”
Section: Introductionmentioning
confidence: 99%